Digital Religion and Media Economics: Concentration and Convergence in the Electronic Church - Ward, Mark (Journal of Religion, Media and Digital Culture, 2018)
The economics that push every medium toward market concentration have historically done likewise to every religious medium. “Online religion” is now, in its turn, colonized by an “electronic church” industry that, due to media deregulation, is dominated by religious media conglomerates—through whom North Americans are most likely to engage in digital religion. The largest conglomerate alone generates 110 million computer sessions and 79 million mobile sessions per month. This study reviews the economics of media concentration and applications to religious media, surveys the digital footprint of the institutional electronic church, and advocates integration of media practices into Digital Religion Studies.